Myocardial ischemia-reperfusion in rats: reduction of infarct size by either supplemental physiological or pharmacological doses of melatonin - Sahna, E; Acet, A; Ozer, MK; Olmez, E (Wiley, 2002)
Myocardial ischemia reperfusion (I/R) represents a clinically relevant problem associated with thrombolysis, angioplasty and coronary bypass surgery. I/R injury is believed to be a consequence of free radical generation in the heart especially during the period of reperfusion. The pineal secretory product, melatonin, is known to be a potent free radical scavenger and pharmacological concentrations have been shown to reduce the I/R-induced cardiac damage in isolated rat hearts. However, the physiological role of melatonin in the prevention of this damage is unknown. Rats were pinealectomized or sham-operated (control) 2 months before the I/R studies. To produce cardiac damage, the left main coronary artery was occluded for 30 min, followed by 120 in reperfusion, in anesthetized rats. Infarct size, expressed as the percentage of the risk zone, was found significantly higher in pinealectomized rats (49 +/- 4%) than in the control group (34 +/- 6%). Melatonin administration (4 mg/kg, either before ischemia or reperfusion) to pinealectomized rats significantly reduced the infarct size values and returned the to the control values. On the other hand, melatonin administration (4 mg/kg) to sham-operated rats failed to attenuate significantly the I/R-induced infarct size. These results suggest that physiological melatonin concentrations are important in reducing the I/R-induced myocyte damage, while pharmacological concentrations of melatonin did not add to the beneficial effect. As melatonin levels have been reported to decrease with age, melatonin replacement therapy may attenuate I/R-induced myocardial injury, especially in older patients.
Keywords: infarct size; melatonin; myocardial ischemia-reperfusion; pinealectomy